2005
DOI: 10.1111/j.1399-6576.2005.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydroxyethyl starch on lipopolysaccharide‐induced tissue nuclear factor kappa B activation and systemic TNF‐α expression

Abstract: Lower doses of HES may inhibit tissue NF-kappaB activation and systemic TNF-alpha elevation after LPS challenge, which might be helpful during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…Hydroxyethyl starch seems to exert beneficial anti-inflammatory effects (Handrigan et al 2005;Boldt 2006;Gurfinkel et al 2003), and to inhibit cytokines in experimental sepis (Tian et al 2005). The use of hypertonic saline has also been shown to reduce systemic and pulmonary inflammatory responses (reduced levels of TNF-Į and IL-6) ( Gurfinkel et al 2003).…”
Section: Ct-i Alb-i Hes-i Ct-ii Hsh-ii Ct-iiimentioning
confidence: 99%
“…Hydroxyethyl starch seems to exert beneficial anti-inflammatory effects (Handrigan et al 2005;Boldt 2006;Gurfinkel et al 2003), and to inhibit cytokines in experimental sepis (Tian et al 2005). The use of hypertonic saline has also been shown to reduce systemic and pulmonary inflammatory responses (reduced levels of TNF-Į and IL-6) ( Gurfinkel et al 2003).…”
Section: Ct-i Alb-i Hes-i Ct-ii Hsh-ii Ct-iiimentioning
confidence: 99%
“…Current medium‐molecular‐weight HES solutions seem to be more efficacious. Previous studies in our laboratory have indicated that low doses of HES 200/0.5 can downregulate inflammatory mediators during endotoxemia (4, 5). Recently, HES 130/0.4, a new HES solution, has been developed.…”
mentioning
confidence: 99%
“…demonstrated that a lower dose of HES 200 (3.75 and 7.5 mL/kg) significantly suppresses LPS-induced NF-κB activation in four tissues (lungs, liver, heart, and kidneys). However, 15 mL/kg HES 200 inhibits NF-κB activity only in the lungs and liver, and 30 mL/kg HES 200 exerts no effect in any measured organs [35,37]. The effect of GEL on the inflammatory response was similar at three doses (7.5, 15 and 30 mL/kg) [38].…”
Section: Discussionmentioning
confidence: 99%